2023
DOI: 10.1051/0004-6361/202245140
|View full text |Cite
|
Sign up to set email alerts
|

Whistler waves generated inside magnetic dips in the young solar wind: Observations of the search-coil magnetometer on board Parker Solar Probe

Abstract: Context. Whistler waves are electromagnetic waves produced by electron-driven instabilities, which in turn can reshape the electron distributions via wave–particle interactions. In the solar wind they are one of the main candidates for explaining the scattering of the strahl electron population into the halo at increasing radial distances from the Sun and for subsequently regulating the solar wind heat flux. However, it is unclear what type of instability dominates to drive whistler waves in the solar wind. Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 74 publications
2
22
0
Order By: Relevance
“…Wave amplitudes peaked at 2 nT representing up to 0.05 of the background magnetic field magnitude. The polarization of these waves was found to be predominantly quasi-parallel to the background magnetic field confirming the statistics reported by Cattell et al (2020) and Froment et al (2022). The quasi-parallel propagation appears to be the predominant mode of the observed whistler waves in the solar wind in all the range of heliocentric distances covered by observations by PSP and Solar Orbiter: the probability to observe waves with wave normal angle above 50°is less than 0.01 (Tong et al 2019;Kretzschmar et al 2021;Cattell et al 2022).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Wave amplitudes peaked at 2 nT representing up to 0.05 of the background magnetic field magnitude. The polarization of these waves was found to be predominantly quasi-parallel to the background magnetic field confirming the statistics reported by Cattell et al (2020) and Froment et al (2022). The quasi-parallel propagation appears to be the predominant mode of the observed whistler waves in the solar wind in all the range of heliocentric distances covered by observations by PSP and Solar Orbiter: the probability to observe waves with wave normal angle above 50°is less than 0.01 (Tong et al 2019;Kretzschmar et al 2021;Cattell et al 2022).…”
Section: Discussionsupporting
confidence: 84%
“…There was strong whistler wave activity throughout much of PSP's Encounter 1 and several authors have reported on these observations (Agapitov et al 2020;Cattell et al 2021aCattell et al , 2021bCattell et al , 2022Dudok de Wit et al 2022;Froment et al 2022). Recently, whistler waves observed during Encounter 1 have been linked to the scattering of strahl at distances less than 50R e (less than 0.25 au) from the Sun (Cattell et al 2021a(Cattell et al , 2021bJagarlamudi et al 2021) including some of the cases reported in this article.…”
Section: Introductionsupporting
confidence: 53%
“…These indications consist in statistically significant observations of the halo population with perpendicular temperature anisotropy (Pierrard et al 2016;Wilson et al 2019;Jagarlamudi et al 2020;Wilson et al 2020;Salem et al 2023) and preferential occurrence of whistler waves in association with isotropic or perpendicular anisotropic halo (Tong et al 2019a(Tong et al , 2019bJagarlamudi et al 2020). The recent reports of sunward and anti-sunward-propagating whistler waves in the near-Sun solar wind are also of relevance (Mozer et al 2020;Froment et al 2023).…”
Section: Introductionmentioning
confidence: 91%
“…Since whistler waves in the solar wind have typical amplitudes below a few percent of the background magnetic field, we expect the typical efficiency of local electron heat flux suppression to be within about 10%. The recent reports of sunward whistler waves with amplitudes of 0.1B 0 (Mozer et al 2020;Froment et al 2023) indicate, however, that the local electron heat flux suppression may occasionally exceed 60%.…”
Section: Tablementioning
confidence: 97%
“…The statistical study of whistler properties by Froment et al. (2023) revealed that most of the whistler wave packets recorded during Encounter 1 were quasi‐parallel to the background magnetic field: 97% had WNA between 0 and 25°. Whistler waves were observed in the frequency range from the local lower hybrid frequency f lh up to 0.2 f ce .…”
Section: Introductionmentioning
confidence: 99%